2022
DOI: 10.3390/molecules27186080
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Ultrasonic—Assisted Extraction (UAE) Method Using Natural Deep Eutectic Solvent (NADES) to Increase Curcuminoid Yield from Curcuma longa L., Curcuma xanthorrhiza, and Curcuma mangga Val.

Abstract: This study aims to optimize ultrasonic-assisted natural deep eutectic solvents (NADES) based extraction from C. longa. Choline chloride-lactic acid (CCLA-H2O = 1:1, b/v) was used to investigate the impact of various process parameters such as solvent’s water content, solid loading, temperature, and extraction time. The optimal yield of 79.635 mg/g of C. longa was achieved from extraction in 20% water content NADES with a 4% solid loading in 35 °C temperature for 1 h. Peleg’s model was used to describe the kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…However, the extract required additional separation and chromatographical purification for a high-quality product (Rachmaniah et al, 2021). Additionally, Rosarina et al (2022) The extraction and solubilisation of curcumin can be accomplished and enhanced using NaDES (ChCl/ lactic acid) as a compatible auxiliary to surfactant-free microemulsions such as ethanol/triacetin mixtures (Huber et al, 2021). The extraction yield (90%) and solubilisation (2-fold) are outstanding despite the highly hydrophobic nature of curcumin and the very polar medium.…”
Section: Curcuminoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the extract required additional separation and chromatographical purification for a high-quality product (Rachmaniah et al, 2021). Additionally, Rosarina et al (2022) The extraction and solubilisation of curcumin can be accomplished and enhanced using NaDES (ChCl/ lactic acid) as a compatible auxiliary to surfactant-free microemulsions such as ethanol/triacetin mixtures (Huber et al, 2021). The extraction yield (90%) and solubilisation (2-fold) are outstanding despite the highly hydrophobic nature of curcumin and the very polar medium.…”
Section: Curcuminoidsmentioning
confidence: 99%
“…Additionally, Rosarina et al . (2022) optimised the curcuminoid extraction using NADES (ChCl/lactic acid, water 20%) supported with UAE. Separation and crystallisation resulted in good yields.…”
Section: Extraction Of Phytochemicalsmentioning
confidence: 99%
“…21 Additionally, UAE had previously been utilised to unear th metabolites, ecological pigments, and bioactive compounds from other curcuma species. [33][34][35][36][37][38][39][40] The detection of bioactive phytoconstituents in the GC-MS examination of rhizome chloroform extracts of Curcuma caesia Roxb. and Curcuma angustifolia Roxb.…”
Section: Gc-ms Assessment Findingsmentioning
confidence: 99%
“…Several studies have reported successful extraction of various classes of bioactive compounds, including phenolic acids, flavonoids, alkaloids and essential oils, using ultrasound-assisted techniques [14][15][16][17][18]. For instance, UAE has been utilized to extract phenolic compounds such as resveratrol, quercetin and curcumin from different plant sources [19][20][21][22]. The enhanced extraction efficiency provided by UAE can contribute to the development of high-value natural extracts and facilitate the utilization of plant-derived bioactive compounds in various industries [3].…”
Section: Introductionmentioning
confidence: 99%